Autoeficácia e satisfação no trabalho de docentes-alunos do parfor - FERREIRA, Enizete Andrade (Universidade Federal do Pará, 2019)
This research deals with the categories selfefficacy and satisfaction in the work in the light of the Cognitive Social Theory of Albert Bandura that will subsidize the study with teachers in formation by the National Plan of Formation of Teachers (Parfor). The clipping for study are teachersstudents of the pedagogy course (4th and 5th period) of three poles in the state of Pará: Belém, Abaetetuba and Cametá. The objective is to analyze teacher selfefficacy and job satisfaction of teachers in PARFOR Training. From a theoretical and methodological point of view, a systematic review of studies aimed at selfefficacy and job satisfaction subsidized by the Cognitive Social Theory was carried out in order to strengthen the research corpus; it is also a field research of an exploratory and descriptive nature of quantitative and qualitative nature; characterization questionnaire, Likerttype scales and interviews were used as data collection instrument. The quantitative data were processed by the analysis of Factorial Analysis (AF) and Analysis of Correspondence (CA), as well as descriptive analysis with measures of central tendency and in the qualitative analysis was performed Content Analysis (CA) according to Bardin with the software NVIVO 10. The results of the Systematic Review indicate the relationship of different variables in relation to the categories studied. In terms of selfefficacy, the most frequent subcategories were: teacher performance (f = 6), teacher collaboration (f = 2), selfesteem (f = 2), motivation (F = 2) and burnout (f = 2) were the most frequent with focus on the two categories simultaneously (selfefficacy and satisfaction). Results of the factorial analysis returned from the variables (questions) satisfactorily by the retained factors, already present commonality values higher than 0.30 (30%) that all variables present at least moderate correlation (r ≥0.50); in the correspondence analysis, the values of the descriptive level (p) lower than the level of significance of 0.05 (5%) and of the Beta (β) criterion greater than or equal to 3, point out that there is dependence on both the variables and their categories . The process of coding by semantic clustering (content analysis), resulted in final categories related to selfefficacy: (1) Beliefs and Strategies of Education (f = 36); Selfevaluation (f = 11), Peer Collaboration (f = 12), which synthesize participants' perceptions regarding this category and job satisfaction, which resulted in the final categories: (1) Emotional States (f = 43); professional valuation or devaluation (f = 25) and practice and teacher training (f = 7). It was verified that, in the educational context, the categories selfefficacy and satisfaction at work can influence the teaching actions.